A 26-Year-Old Female with Systemic Mastocytosis with Associated Myeloid Neoplasm with Eosinophilia and Abnormalities of PDGFRB, t(4;5)(q21;q33). (25th August 2016) - Brown, Laura E.; Zhang, Da; Persons, Diane L.; Yacoub, Abdulraheem; Ponnala, Shivani; Cui, Wei
Abstract : Various translocations involving the PDGFRB gene are identified in myeloid neoplasms. However, the PRKG2/PDGFRB fusion gene associated with t(4;5)(q21;q33) has previously been reported in only 3 patients. We present the case of a 26-year-old woman with microcytic anemia, basophilia, thrombocytosis, and massive splenomegaly, who was found to have systemic mastocytosis and associated clonal hematological non-mast cell lineage disease (SM-AHNMD), with myeloid neoplasm with PRKG2/PDGFRB rearrangement. Initial findings included basophilia (37%, 4.1 k/μ L), hypercellular marrow with eosinophilia, and increased and atypical megakaryocytes, suggestive of myeloproliferative neoplasm. Additional studies revealed large clusters of CD25 positive mast cells, fulfilling the criteria for the diagnosis of systemic mastocytosis. Consistent with prior reports of this translocation, our patient has responded well to imatinib. This case, in conjunction with others in the literature, suggests a possible connection between t(4;5)(q21;q33) PRKG2/PDGFRB and systemic mastocytosis and highlights their favorable response to imatinib.